1988
DOI: 10.1063/1.341643
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability of ferroelectric KNO3 switching devices during polarization aging

Abstract: The persistent observation of polarization aging during repeated room-temperature switching of metastable thin-film ferroelectric potassium nitrate capacitors has led to the conjecture that the observed polarization decay is a direct consequence of a concomitant phase III to phase II structural transformation. Appropriate large area thin-film devices have been fabricated to perform this x-ray diffraction study of the phase stability of ferroelectric KNO3 devices during in situ electrical switching. As the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…The diffraction peaks of KNO 3 at 2θ = 29.85°of (003) reflection for ferroelectric phase III and 2θ = 29.2° of (012) reflection for phase II have already been reported in literature [30, 31]. These reflections have also been observed in the X‐ray diffraction scan of the 50 wt% composite film as shown in Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The diffraction peaks of KNO 3 at 2θ = 29.85°of (003) reflection for ferroelectric phase III and 2θ = 29.2° of (012) reflection for phase II have already been reported in literature [30, 31]. These reflections have also been observed in the X‐ray diffraction scan of the 50 wt% composite film as shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…4a. X‐ray diffraction measurements have been done by various researchers [27, 30, 32] to know the crystal structure and values of different phases of KNO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The most common diffraction peaks of phase II at 2θ = 23.57°, 23.83°, 29.40°, 32.33°, and 32.82° were observed in the Kno 3 powder for the planes of (h k l) values (111), (021), (012), (102), and (112), respectively. These peaks have also been seen in the Xrd patterns of Kno 3 taken by schaffer and Mikkola [41]. The lattice parameters a, b, and c for Kno 3 have been calculated from Xrd pattern for pure Kno 3 and were found to be 6.552, 5.472, and 9.028 Å, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…It has been reported that the preparation of the composite films of nano 2 , selenide with PVa using solvent cast technique was helpful in controlling the growth of nano 2 , and selenide nanoparticles [10], [22]. Many studies using techniques such as far infrared [25], neutron diffraction [26], inelastic neutron scattering [27], raman spectroscopy [28], [29], X-ray [30]- [32], differential scanning calorimetric [33]- [35], dielectric [36], electrical and thermal conductivity [36], [37], and ferroelectric [38]- [41], have been carried out in the past by various researchers to examine the nature of the phase transitions in Kno 3 . The technological interest in Kno 3 thin films originates due to the reason that these films have low operating voltage and fast switching response.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits ferroelectric behaviour in phase III. KNO 3 has been found to be ferroelectric in bulk form [7] and in thin fused layers [8] quenched to room temperature.…”
Section: Introductionmentioning
confidence: 98%